2021
DOI: 10.1073/pnas.2101852118
|View full text |Cite
|
Sign up to set email alerts
|

An ultra-high-affinity small organic ligand of fibroblast activation protein for tumor-targeting applications

Abstract: We describe the development of OncoFAP, an ultra-high-affinity ligand of fibroblast activation protein (FAP) for targeting applications with pan-tumoral potential. OncoFAP binds to human FAP with affinity in the subnanomolar concentration range and cross-reacts with the murine isoform of the protein. We generated various fluorescent and radiolabeled derivatives of OncoFAP in order to study biodistribution properties and tumor-targeting performance in preclinical models. Fluorescent derivatives selectively loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 43 publications
6
73
0
Order By: Relevance
“…The modified synthetic consensus FAP DNA vaccine synergized with other tumor antigen-specific vaccine therapies in tumor-bearing mice ( 92 ). Moreover, adoptive transfer of FAP-specific chimeric antigen receptor to T cells proved to be effective in restraining tumor growth in preclinical models ( 93 ). In addition, FAP-targeting oncolytic adenovirus in tumor-bearing mice enhanced anti-tumor immunity by activating endogenous T cells to attack FAP + stromal cells.…”
Section: Therapeutic Targeting Of Cafsmentioning
confidence: 99%
“…The modified synthetic consensus FAP DNA vaccine synergized with other tumor antigen-specific vaccine therapies in tumor-bearing mice ( 92 ). Moreover, adoptive transfer of FAP-specific chimeric antigen receptor to T cells proved to be effective in restraining tumor growth in preclinical models ( 93 ). In addition, FAP-targeting oncolytic adenovirus in tumor-bearing mice enhanced anti-tumor immunity by activating endogenous T cells to attack FAP + stromal cells.…”
Section: Therapeutic Targeting Of Cafsmentioning
confidence: 99%
“…Results from a phase I clinical study and pharmacokinetic analysis of the humanized anti-FAP antibody (sibrotuzumab) further revealed that it is well tolerated in humans and is specifically concentrated in the tumor stroma, with limited absorption in normal tissues (107). Moreover, Millul et al (106). described a ligand with ultrahigh affinity for FAP (OncoFAP) that is used for precise diagnosis and treatment of FAP + tumors.…”
Section: Targeted Drugs and Nanodrugs Based On Antibodies To Fapmentioning
confidence: 99%
“…The multifunctional RPS-309 could be a useful tool for the study of the relationship between FAPI structure and substrate activity in the future. In addition, an ultra-high-affinity small organic ligand (OncoFAP), a carboxylic acid moiety, for FAP targeting was very recently reported [ 120 ]. The OncoFAP was chemically modified at position 8 on quinoline moiety of the FAPI molecule and further functionalization with the chelator DOTAGA, leading to a FAP-based ligand with a high dissociation constant ( K d ) ranging from 0.68 nM for human FAP to 11.6 nM for murine FAP.…”
Section: Development Of Radiolabeled-based Fap Tracers For Tumor Stroma Mediated Nuclear Imaging and Radionuclide-based Therapymentioning
confidence: 99%